Efficient non-doped deep blue organic light emitting diodes with high external quantum efficiency and a low efficiency roll-off based on donor-acceptor molecules. (July 2017) - Islam, Amjad; Wang, Qiang; Zhang, Lei; Lei, Tao; Hong, Ling; Yang, Rongjuan; Liu, Zhiyang; Peng, Ruixiang; Liao, Liang-Sheng; Ge, Ziyi
Abstract: Two phenanthroimidazole derivatives containing triphenylamine, carbazole and pyrene units were designed and synthesized. Highly efficient non-doped deep blue organic light emitting diodes (OLEDs) were fabricated by using these materials as emissive layer. The non-doped devices demonstrated high efficiency (4.24 cd/A, 3.67 lm/W, 4.66%), low efficiency roll-off at higher current densities, and stable deep blue emissions with CIEy around 0.10, which are excellent results for deep-blue OLED devices. This study reveals that the combination of phenanthroimidazole and donor-linker-acceptor strategy has a great potential for developing high performance deep-blue OLEDs. Highlights: Novel emissive molecules containing phenanthroimidazole, triphenylamine, carbazole and pyrene units are developed. Deep blue emission is exhibited by these fluorescent materials. High thermal stability of materials and low operating voltage of device are observed. Non-doped OLEDs are constructed with high efficiency and low roll-off.